Factors that Influence the use of Management Accounting on SME Performance in the city of Medan - Ardila, Isna; Sembiring , Masta; Kalsum, Umi (Universitas Muhammadiyah Sorong, 2024)
The aim of this research is to examine the influence of the use of management accounting on SME performance, and environmental uncertainty, information technology, quality of human resources and innovation as factors that influence the use of management accounting. Descriptive quantitative research method, namely the results of processing data and then representing it. The population of this research is SMEs from various business sectors spread across the city of Medan. The sample was taken using a purposive sampling technique as many as 33 SMEs in the city of Medan. The Structural Equation Modeling (SEM) equation model is used for the data analysis method. Information technology influences the use of management accounting, environmental uncertainty, human resources and innovation do not influence the use of management accounting. The use of management accounting influences the performance of SMEs.